2016
DOI: 10.5897/ajbm2016.8031
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality and organizational commitment : A study on the public schools teachers in Menoufia (Egypt)

Abstract: Due to its significant impact on organizations' survival and success, workplace spirituality has gained popularity in both academic and work environments over the last decade. This popularity has been created and maintained because of employees' feeling of hyper stress and anxiety stemming from the very high demands and expectations imposed by their organizations. In reaction to such high targets, employees tend to increase their levels of absenteeism, leave their jobs with less provocation, raising rates of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Kadyschuk, 1997;Bogler & Somech, 2004;Crosswell, 2006;Dee, Henkin, & Singleton, 2006;William, 2011;Devos & Tuytens, 2013;Garipaĝaoĝiu, 2013;Hamid, Nordin, Adnan, & Sirun, 2013;Ayale, 2014;Mousa & Alas, 2016). Lack of study on teachers' organizational commitment in Merauke district makes this present study robust.…”
Section: Introductionmentioning
confidence: 68%
“…Kadyschuk, 1997;Bogler & Somech, 2004;Crosswell, 2006;Dee, Henkin, & Singleton, 2006;William, 2011;Devos & Tuytens, 2013;Garipaĝaoĝiu, 2013;Hamid, Nordin, Adnan, & Sirun, 2013;Ayale, 2014;Mousa & Alas, 2016). Lack of study on teachers' organizational commitment in Merauke district makes this present study robust.…”
Section: Introductionmentioning
confidence: 68%
“…Other studies (see Gutierrez, Candela, & Carver, 2012;Rego & Pina e Cunha, 2008) also show a tendency for continuance commitment to score the lowest. Mohamed and Ruth (2016) found that meaningful work positively affects continuance commitment amongst public school teachers in Egypt. Other studies (see Chawla & Guda, 2010;Javanmard, 2012;Osman-Gani, Hashim, & Ismail, 2013) also found that sense of meaning and sense of purpose were associated with the affective and normative commitment of employees.…”
Section: Outline Of the Resultsmentioning
confidence: 96%
“…'Workplace spirituality' relates the desires of employees to live integrated, holistic lives, including recognition and acceptance of their spirituality in the work context (Aravamudhan & Khrishmaveni, 2014). By analysing literature (see BinBakr & Ahmed, 2015;Mohamed & Ruth, 2016;Wainaina et al, 2014) three distinct components of workplace spirituality emergesense of meaning, sense of purpose and a sense of community or connectedness with others. For the sake of this study, workplace spirituality can be explained as a dynamic process http://www.sajhrm.co.za Open Access…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…According to Mousa and Alas (2016), the concept of workplace spirituality has become a buzzword in contemporary organizations. Further, organizations consist of group of people and the spiritual needs of individuals should fulfill accordingly (Krishnalumar & Neck, 2002).…”
Section: Workplace Spiritualitymentioning
confidence: 99%
“…Otherwise, individuals become dissatisfied and organizational spirituality becomes low. Bringing employees' heart, soul, mind, and body into one place is very much important for both individual and organizational success (Mousa & Alas, 2016).…”
Section: Workplace Spiritualitymentioning
confidence: 99%